Tribological characterization of laminated hybrid AA1050/TiC/Graphite composite bars - Mohammad Heydari Vini; Dheyaa J. Jasim; S. Mohammad Sajadi; Saeed Daneshmand; Ahmed Salah Al-Shati; Navid Nasajpour-Esfahani; M. Hekmatifar (Journal of Materials Research and Technology, 2023)
Hybrid composites (HC) refer to a type of material that combines aluminum (Al), titanium carbide (TiC), and graphite (Gr) at the nano level. These HC have shown promise in applications requiring high strength, wear resistance (WR), and tribological performance, such as automotive, aerospace, and industrial sectors. In this study, these HC are made using a combination of Powder metallurgy (PM) and accumulative press bonding (APB) processes have been developed. This is the first time that the wear resistance of a hybrid metal matrix composite fabricated with Gr as a solid lubricant has been done and thid is the novelty of this study. In fact, the presence of TiC nanoparticles (NP) provides improved mechanical properties, such as hardness (Hr), strength, and WR for HC. On the other hand, Gr acts as a solid nano-lubricant (NLU) in HC, reducing friction and WR during sliding contact. The presence of Gr-NP also helps to form a durable Gr-nanolayer on tribo surfaces and further improves the WR of HC. This study used a scanning electron microscope (SEM). The results demonstrated that incorporating TiC- NP reduced the WR rate and promoted NL development at extended sliding distances, creating a durable TiC/Gr HC on the TS. Finally, the improved WR of Al/TiC/Gr-HC can be attributed to the stability of the Gr-NL on the TS.